Simple, Fast and Selective Detection of Adenosine Triphosphate at Physiological pH Using Unmodified Gold Nanoparticles as Colorimetric Probes and Metal Ions as Cross-Linkers - Huan Pang; Lin Liu; Chunying Xu; Ting Sun; Sujuan Li; Ning Xia; Dehua Deng (Sensors, 2012)
We report a simple, fast and selective colorimetric assay of adenosine triphosphate (ATP) using unmodified gold nanoparticles (AuNPs) as probes and metal ions as cross-linkers. ATP can be assembled onto the surface of AuNPs through interaction between the electron-rich nitrogen atoms and the electron-deficient surface of AuNPs. Accordingly, Cu2+ ions induce a change in the color and UV/Vis absorbance of AuNPs by coordinating to the triphosphate groups and a ring nitrogen of ATP. A detection limit of 50 nM was achieved, which is comparable to or lower than that achievable by the currently used electrochemical, spectroscopic or chromatographic methods. The theoretical simplicity and high selectivity reported herein demonstrated that AuNPs-based colorimetric assay could be applied in a wide variety of fields by rationally designing the surface chemistry of AuNPs. In addition, our results indicate that ATP-modified AuNPs are less stable in Cu2+, Cd2+ or Zn2+-containing solutions due to the formation of the corresponding dimeric metal-ATP complexes.